THE ROLE OF FACEBOOK AS A SOCIAL MEDIA MARKETING ON HOUSEWIVES’ START-UP BUSINESS - Wardana, Ludi Wishnu (Universitas Ciputra Surabaya, 2018)
Social media marketing is one of several marketing models, and as the name suggests, it utilizes social media, which is used by most people nowadays, to market or promote a product, a service, a brand, or an issue. This study aims to analyze how influential is the role of Facebook to several housewives’ start-up business. This study uses qualitative approach, which utilizes interviews in order to understand the marketing strategy through social media that is implemented by several housewives’ start-up business. The marketing strategy that is implemented by these housewives’ start-up business corresponds with developments in the current age, in which everything is IT-based. The Facebook as a social media marketing that these housewives’ start-up business implement can be categorized as a good marketing strategy. This can be proven with the achievement of outputs that are created during the implementation of these housewives’ social media marketing strategy and with positive impacts that this strategy has created, especially on the increase of productivity, profit, competitiveness, and competence, as well as on the creation of a good image among their enterprises. However, the problem for these housewives’ start-up business comes from their own inactivity in the marketing process, and this affects their customers as the customers find it hard to find information about these enterprises. Thus, it can be concluded that the marketing strategy that these housewives’ start-up business implement, which is social media marketing, has an important role in the success of their enterprises.